2006
DOI: 10.1017/s003118200500973x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anthelmintic efficacy of plant cysteine proteinases against the rodent gastrointestinal nematode, Trichuris muris

Abstract: (2006) In vitro and in vivo anthelmintic efficacy of plant cysteine proteinases against the rodent gastrointestinal nematode, Trichuris muris. Parasitology, 132 (5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 37 publications
(51 reference statements)
9
89
1
1
Order By: Relevance
“…Although the plant cysteine proteinases, with the exception of actinidain, show anthelmintic activity against P. muricola in vitro, and earlier studies have shown significant in vivo efficacy of papaya latex against the adult worms of H. polygyrus (Stepek et al manuscript in preparation) and T. muris (Stepek et al 2006), we initially failed to detect efficacy of papaya latex against P. muricola in vivo. However, when the mice were pre-treated with the antacid cimetidine, papaya latex had a significant anthelmintic effect.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although the plant cysteine proteinases, with the exception of actinidain, show anthelmintic activity against P. muricola in vitro, and earlier studies have shown significant in vivo efficacy of papaya latex against the adult worms of H. polygyrus (Stepek et al manuscript in preparation) and T. muris (Stepek et al 2006), we initially failed to detect efficacy of papaya latex against P. muricola in vivo. However, when the mice were pre-treated with the antacid cimetidine, papaya latex had a significant anthelmintic effect.…”
Section: Discussionmentioning
confidence: 78%
“…This was followed by complete digestion of the cuticle by 120 min. As with H. polygyrus (Stepek et al 2005) and T. muris (Stepek et al 2006), the adult worms of P. muricola were not affected by the cysteine proteinase from kiwi fruit, actinidain (Fig. 3D).…”
Section: R E S U L T Smentioning
confidence: 75%
See 2 more Smart Citations
“…However, to our knowledge, the current study is the first (i) to establish, unequivocally, that it is upon the cysteine proteinases present in the latex that the anthelmintic efficacy of papaya latex depends, and (ii) to provide evidence that the mechanisms of action in vivo and in vitro are essentially indistinguishable. In vitro studies (Stepek et al 2005(Stepek et al , 2006(Stepek et al , 2007 have demonstrated that cysteine proteinases attack the protective cuticle of the nematode, rapidly leading to complete dissolution of the parasite, a mechanism of action that differs from all the current anthelmintic drugs (Sangster and Gill, 1999 ;Martin and Robertson, 2000). This effect was similar to that described previously for 3 other gastrointestinal nematodes, H. polygyrus (Stepek et al 2005), T. muris (Stepek et al 2006) and Ascaris suum (Robbins, 1930 ;Berger and Asenjo, 1939), indicating that plant cysteine proteinases have a broad spectrum of activity against GI nematodes in vitro.…”
Section: Discussionmentioning
confidence: 99%